Detection of Epstein–Barr virus in leucoreduced blood products. Issue 2 (18th September 2015) - Trottier, H.; Delage, G.; Hu, J.; Robitaille, N.; Buteau, C.; Tucci, M.; Lacroix, J.; Alfieri, C.
Abstract : This study examined the prevalence of three human herpesviruses (HHV), namely HHV‐4 (Epstein–Barr virus/EBV), HHV‐6b and HHV‐7 in leucoreduced blood products obtained from the Sainte‐Justine Hospital blood bank. A total of 100 specimens, including 34 red blood cell concentrates, 33 platelet bags and 33 plasma units, were collected and screened by a sensitive PCR assay using virus‐specific primers. Positive units were then retested by quantitative PCR. Of the 100 specimens, one platelet unit tested positive for EBV.